Sticky Floor, Glass Ceiling and Queen Bee: The triple barrier imposed by the sexist economy (Research, Society and Development, 2021)
Capitalism has its bases founded on the sexist economy, where women represent a means for the acquisition of easy profit. Based on this premise, the present work aims, through bibliographic research, to study the “sticky floor”; the “glass ceiling” and the “queen bee” phenomenon as a triple barrier encountered by women to reach command positions, as well as the consequences of this economic model.